1000 AMAZING DINOSAUR FACTS - Derrick, Stevie; Lomax, Dean; Woodward, John, 1954-; Benton, Adam; Bull, Peter; Jackson-Carter, Stuart; Lewis, Arran; Murray, Naomi; Scott, Gus (London : Dorling Kindersley Limited, 2023)
Discover the fastest, the slowest, the deadliest, and the downright weirdest dinosaurs ever to roam the planet. Did you know that the largest dinosaur was longer than a tennis court but its babies were no bigger than a newborn human baby? That the smallest dinosaur weighed less than a teaspoon of sugar? Or that the largest flying reptile was as tall as a giraffe, with wings the size of a small plane? Packed with mind-boggling facts, this book will take you back to a world like no other.
Includes index
Keywords: Dinosaurs -- Miscellanea; Fossils -- Miscellanea; Paleontology -- Miscellanea; Miscellanies; Curiosities and wonders; Trivia and miscellanea